The regulation of totipotency transcription: Perspective from in vitro and in vivo totipotency - Xu, Haiyan; Liang, Hongqing (Frontiers in Cell and Developmental Biology, 2022)
Totipotency represents the highest developmental potency. By definition, totipotent stem cells are capable of giving rise to all embryonic and extraembryonic cell types. In mammalian embryos, totipotency occurs around the zygotic genome activation period, which is around the 2-cell stage in mouse embryo or the 4-to 8-cell stage in human embryo. Currently, with the development of in vitro totipotent-like models and the advances in small-scale genomic methods, an in-depth mechanistic understanding of the totipotency state and regulation was enabled. In this review, we explored and summarized the current views about totipotency from various angles, including genetic and epigenetic aspects. This will hopefully formulate a panoramic view of totipotency from the available research works until now. It can also help delineate the scaffold and formulate new hypotheses on totipotency for future research works.